A Functional BCI Model by the P2731 Working Group: Transducer. Issue 3 (3rd July 2021) - Sahonero-Alvarez, Guillermo; Singh, Avinash Kumar; Sayrafian, Kamran; Bianchi, Luigi; Roman-Gonzalez, Avid
ABSTRACT: A Brain-Computer Interface (BCI) can be considered as a technology that allows for alternative means of communication between humans and their environment using thoughts and intentions. The structure of this interface is composed of various stages, beginning with the acquisition of the brain signals, followed by several processing stages, and leading to the generation of feedback signals. The development of a BCI system involves a diverse set of expertise in order to produce a unique environment for continuous innovations. However, such diversity in technical background and expertise may lead to confusion in the terminology used by the community. As such, the IEEE P2731 WG has been tasked with the development of a functional model to facilitate the understanding of a BCI system. In this paper, we focus on the description of the functional elements that belong to the transducer stage of a BCI.